Polystyrene-based sulfonium salt and photoresist composition thereof
By using polystyrene-based sulfonium salt polymer as the acid generator or main material of the photoresist, the problem of acid diffusion in chemical amplified photoresist is solved, and the photoresist performance with high resolution and low line width roughness is achieved.
Patent Information
- Application Number
- CN202211436603.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-24
- Filing Date
- 2022-11-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The existing chemical amplified photoresist acid diffusion problem after exposure leads to poor graphics quality, limiting the development of lithography technology.
Polystyrene-based sulfonium salt is used as the acid generator or host material of the photoresist, and the sulfonium salt is decomposed by light to generate acid or change solubility, thereby realizing pattern transfer.
It effectively avoids the problem of acid diffusion, improves the resolution of the photoresist and the line width and roughness of the pattern, and is suitable for high-resolution photolithography technology.
Smart Images

Figure CN116162187B_ABST
Abstract
Description
[0001] The present invention claims priority to a prior application with patent application number 202111407329.6, entitled “Polystyrene-based sulfonium salt and photoresist composition thereof”, filed with the State Intellectual Property Office of China on November 24, 2021. The entire text of the prior application is incorporated herein by reference. Technical Field
[0002] The invention belongs to the field of material technology, and in particular relates to a polystyrene-based sulfonium salt and photoresist composition. Background Art
[0003] With the rapid development of the semiconductor industry, the integration of semiconductor devices is getting higher and higher, and the resolution required to be achieved by photolithography technology is also getting higher and higher. The quality of high-resolution photolithography patterns also puts forward higher requirements, especially the line width roughness (LWR) and line edge roughness (LER) of the patterns are becoming more and more stringent. Photoresist is a key material for transferring photolithography patterns during the processing of semiconductor devices. The photoresist is coated on different substrates, and after being irradiated with energy such as light beams, electron beams, ion beams or x-rays, the solubility changes, and then the corresponding pattern is transferred to the substrate through development and etching processes. The resolution that can be achieved by the pattern formed by the photoresist has a decisive influence on the integration of the device. The comprehensive performance of the photoresist needs to match the development of current photolithography technology.
[0004] At present, conventional high-resolution photoresists all use chemical amplification glue. The concept of "chemical amplification" was proposed by IBM in 1982, in which photoacid generator (PAG) is a key component in the photoresist component. The so-called "chemical amplification" means that PAG decomposes to produce acid after illumination, and the acid triggers a series of chemical reactions, so that the solubility of the photoresist material in the illuminated area and the non-illuminated area changes significantly, and then the pattern transfer can be achieved by developing. Therefore, the acid generation efficiency of the photoacid generator and the distribution uniformity of the acid generator in the material play an important role in the pattern quality. Usually, the photoresist is a mixture composed of a resin main material, PAG and various trace additives. This simple physical mixing can easily cause the acid generator to form unevenly distributed micro-areas in the main material, thereby affecting the edge roughness of the photolithographic pattern. On the other hand, this physical mixing makes it difficult to control the diffusion speed of the generated acid in the main material, which has an adverse effect on the edge roughness of the pattern. These reasons limit the development of chemical amplification photoresists.
[0005] In comparison, non-chemically amplified photoresists do not involve the process of acid diffusion, and can effectively overcome the problem of deteriorating graphic quality caused by acid diffusion. After exposure, the photosensitive groups of this type of photoresist directly undergo chemical reactions, causing the solubility of the exposed substance to change. This single-component non-chemically amplified photoresist avoids problems such as uneven distribution of components and acid diffusion in chemically amplified photoresists. Summary of the invention
[0006] In order to improve the above technical problems, the present invention first provides a polymer of a sulfonium salt of styrene, wherein the repeating unit of the polymer has a structure shown in the following formula (I):
[0007]
[0008] Wherein: x and y represent the percentage of the two monomers in the polymer, x+y=1, 0.3<x≤1, x is, for example, 0.5, 0.72; y is, for example, 0.28, 0.5;
[0009] R1 is selected from a sulfonium salt group; the position of R1 can be para, meta or ortho; R2 is selected from H, OH, halogen (such as Cl, F, I), C 1-15 Alkyl, C 1-15 Alkoxy, aryl; q is an integer selected from 1-5, preferably an integer of 1-3;
[0010] X – is an anion, for example, selected from halide, alkylsulfonate, halogenated alkylsulfonate (such as trifluoromethanesulfonate, perfluoropropylsulfonate, perfluorobutylsulfonate), p-toluenesulfonate, tetrafluoroborate, hexafluorophosphate, bistrifluoromethanesulfonyl imide ion.
[0011] According to an embodiment of the present invention, said R1 is -S + R3R4, wherein R3 and R4 are the same or different and are independently selected from C 1-15 Alkyl, deuterated C 1-15 Alkyl (such as deuterated methyl), aryl, or R3, R4 and the S connected thereto together form a 5-8 membered sulfur-containing heterocyclic group, the sulfur-containing heterocyclic group optionally may further contain 1-2 oxygen or sulfur, the sulfur-containing heterocyclic group is optionally fused with one or two benzene rings; the alkyl, aryl, sulfur-containing heterocyclic group may be substituted by one, two or more (for example, 1-5) R1', each R1' may be the same or different, and are independently selected from H, oxo, nitro, CN, C 1-15 Alkyl, C 1-15 Alkoxy.
[0012] According to an embodiment of the present invention, the R1 is selected from the following groups which are unsubstituted or optionally substituted by one, two or more R1':
[0013]
[0014] in, Represents the bond between the substituent and the benzene ring in the main structure; R 1a and R 1b may be the same or different, and are independently selected from C 1-15 Alkyl, deuterated C 1-15 Alkyl or one, two or more R d Substituted phenyl; each R d are the same or different and are independently selected from H, nitro, C 1-15 Alkyl, C 1-15 Alkoxy; m can be selected from an integer of 0-5; Y is selected from C, O, S, C(=O);
[0015] According to an embodiment of the present invention, R1 may be selected from the following groups which are unsubstituted or optionally substituted by one, two or more R1':
[0016]
[0017] R 1a and R 1b may be the same or different and are independently selected from methyl, ethyl, propyl, isopropyl, butyl, deuterated methyl, R d It can be selected from H, nitro, ethoxy, ethyl, propyl, butyl, isopropyl, isobutyl; m can be 1 or 2; each R1' can be the same or different and independently selected from H, nitro, ethoxy, ethyl, propyl, butyl, isopropyl, isobutyl.
[0018] As an example, the polymer has a repeating unit as shown below:
[0019]
[0020] wherein x and y have the definitions given above.
[0021] According to an embodiment of the present invention, the molecular weight of the polymer is 500-200000 Daltons, such as 1000-100000 Daltons, and for example 5000-50000 Daltons.
[0022] The present invention also provides a method for preparing the above-mentioned polymer, comprising the following steps: preparing a polymer having a repeating unit represented by formula (II):
[0023]
[0024] x, y, q, R2 are as defined above,
[0025] reacting with a sulfoxide compound to obtain a polymer having a repeating unit represented by formula (I);
[0026] Optionally, the polymer having a repeating unit represented by formula (I) is ion exchanged with a corresponding anion solution to obtain polystyrene sulfonium salts with different anions.
[0027] The sulfoxide compound may be R3-S(=O)-R4, for example, selected from:
[0028]
[0029] Among them, R3, R4, R 1a , R 1b , Y, m, x, y have the definitions given above;
[0030] According to an embodiment of the present invention, the reaction may be carried out under the action of a catalyst, and the catalyst may be trifluoromethanesulfonic anhydride or trifluoromethanesulfonic acid;
[0031] According to an embodiment of the present invention, the molar ratio of polystyrene or its copolymer to the sulfoxide compound in the reaction may be 1:(0.3-2), for example 1:(0.5-1), exemplified by 1:0.6.
[0032] According to the present invention, polystyrene is reacted with R3-S(=O)-R4 to obtain a polymer having a repeating unit represented by formula (I);
[0033] According to the present invention, the polymer having the structure represented by formula (II) is prepared by the following method, comprising polymerizing styrene and a compound represented by formula (III) in a certain ratio to obtain a polymer having a repeating unit represented by formula (II),
[0034]
[0035] x, y, q, and R2 are as defined above.
[0036] The present invention also provides application of the polymer as a photoresist acid generator or a main material.
[0037] According to an embodiment of the present invention, when the polymer is used as an acid generator, it can be mixed with other host materials; the other host materials can be any acid-sensitive host materials.
[0038] The present invention also provides a photoresist composition, comprising a polymer whose repeating unit is represented by formula (I).
[0039] According to the present invention, the photoresist composition comprises a polymer having a repeating unit represented by formula (I), a polymer having an acid-sensitive functional group and a photoresist solvent.
[0040] According to the present invention, the photoresist composition is a single-component photoresist, which is composed of a polymer whose repeating unit is represented by formula (I) and a photoresist solvent.
[0041] According to an embodiment of the present invention, in the single-component photoresist, when the x value of the repeating unit represented by formula (I) in the polymer is greater than 0.5, the solubility of the main material changes significantly before and after exposure, and the performance of the photoresist is better.
[0042] According to an embodiment of the present invention, the content of the polymer in the single-component photoresist is 1%-50% of the total mass of the photoresist, and the rest is the photoresist solvent.
[0043] According to an embodiment of the present invention, the photoresist solvent is selected from one or more of the following substances: cyclohexanone, ethyl n-amyl ketone, ethyl isoamyl ketone, ethanol, acetonitrile, isopropanol, and acetone.
[0044] The present invention also provides a photoresist coating, comprising a polymer whose repeating unit is represented by formula (I).
[0045] The present invention also provides a method for preparing the photoresist coating, comprising: spin coating the photoresist composition on a substrate to form a film, thereby obtaining the photoresist coating.
[0046] In one embodiment, the substrate may be a silicon wafer or the like.
[0047] The invention also provides application of the photoresist coating in photolithography.
[0048] In one embodiment, the photoresist coating is used in modern lithography technologies such as 365nm lithography, 248nm lithography, 193nm lithography, extreme ultraviolet lithography, nanoimprint lithography or electron beam lithography; and is particularly suitable for high-resolution lithography technologies such as 193nm, electron beam lithography and extreme ultraviolet (EUV).
[0049] The polymer of the present invention can be dissolved in a polar solvent because it contains a large number of polar functional groups. When the polymer film is exposed, the polar sulfonium salt functional groups decompose, reducing the polarity of the polymer, thereby generating a solubility difference. If a solvent with a relatively large polarity is selected for development, the polymer can be used as a negative photoresist; if a solvent with a relatively small polarity is selected for development, the polymer can be used as a positive photoresist.
[0050] Beneficial Effects
[0051] The invention provides a styrene sulfonium salt polymer shown in formula (I), which can be used as an acid generator or a main material in a photoresist, and contains a photosensitive group sulfonium salt. Under illumination, the sulfonium salt in the polymer decomposes to generate acid, so it can be used as an acid generator. At the same time, the sulfonium salt in the polymer decomposes to form sulfide under illumination, thereby causing a significant change in its solubility, so it can also be directly used as a main material in a photoresist for development. When it is used as a main material, the photoresist does not need to add an additional acid generator, and the problem of acid diffusion in a chemically amplified photoresist can be effectively avoided. The pattern obtained by the photoresist prepared by the styrene sulfonium salt polymer has a very high resolution and a low line width roughness. Based on the styrene sulfonium salt polymer, by changing the sulfonium salt structure, it has a long absorption wavelength, so that the single molecule resin can be used not only for deep ultraviolet lithography, but also for ultraviolet lithography (365nm). BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The scanning electron microscope (SEM) image and the AFM image of the film of compound (1) in Example 2 of the present invention are shown.
[0053] Figure 2 This is the thermogravimetric curve of compound (1) in Example 2 of the present invention.
[0054] Figure 3 This is the UV exposure pattern of the photoresist containing compound (1) in Example 6 of the present invention.
[0055] Figure 4 This is the electron beam exposure pattern (negative resist) of the photoresist containing compound (1) in Example 7 of the present invention.
[0056] Figure 5 This is the UV exposure pattern of the photoresist containing compound (1) in Example 8 of the present invention.
[0057] Figure 6 This is the electron beam exposure pattern (positive photoresist) of the photoresist containing compound (1) in Example 9 of the present invention.
[0058] Definition and explanation of terms
[0059] Unless otherwise defined, all technical and scientific terms herein have the same meaning as commonly understood by one of ordinary skill in the art to which the claimed subject matter belongs.
[0060] "More" means three or more.
[0061] The term "halogen" includes F, Cl, Br or I.
[0062] The term "C 1-15 "Alkyl" is understood to mean a straight-chain or branched saturated monovalent hydrocarbon group having 1 to 15 carbon atoms. For example, "C1-6 The term "alkyl" refers to straight-chain and branched alkyl groups having 1, 2, 3, 4, 5, or 6 carbon atoms. The alkyl group is, for example, methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl, 1,2-dimethylbutyl, or the like or isomers thereof.
[0063] The term "C 1-15 "Alkoxy" is understood to mean -OC 1-15 Alkyl, where C 1-15 Alkyl has the above definition.
[0064] The term "aryl" is understood to mean an aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring having 6 to 20 carbon atoms, preferably "C 6-14 Aryl". For example, phenyl, naphthyl, fluorenyl, anthracenyl, etc. DETAILED DESCRIPTION
[0065] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0066] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0067] Example 1.
[0068] Preparation of polystyrene, the synthetic route is as follows:
[0069]
[0070] Specific steps: Add styrene (100 ml), AIBN (2 g), and then THF (200 ml) into a 500 ml three-necked flask. Bubble for 30 min. React at 70 ° C for 24 h, and drop the reaction solution into methanol for precipitation. The obtained product is vacuum dried. The weight average molecular weight is about 2000 Daltons using GPC test. Styrene with different molecular weights can also be synthesized by other methods or purchased directly.
[0071] Example 2.
[0072] The synthetic route for preparing polymer (1) is as follows:
[0073]
[0074] Specific steps: Add the polystyrene prepared in Example 1 to a 500 ml Schlenk bottle, then add solvent DCM (200 ml) and DMSO (1 eq). Add trifluoromethanesulfonic anhydride (2 eq) dropwise at -40°C under inert gas conditions. Stir overnight at room temperature, dissolve the product with dimethyl sulfoxide, and then dropwise add it into a mixture of n-hexane and ether for precipitation to obtain a polymer (1) with x being 0.72 and y being 0.28, and then dry it in vacuum. 1 H NMR (400MHz, DMSO) δ (ppm) 7.67 (s, 2H), 6.81 (s, 2H), 3.16 (s, 4.3H), 0.9-1.8 (s, 3H).
[0075] Example 3.
[0076] The synthesis route of polymer (2) is as follows:
[0077]
[0078] Specific steps: Add the polystyrene prepared in Example 1 into a 500 ml Schlenk bottle, then add solvent DCM (200 ml) and diphenyl sulfoxide (0.6 eq). Add trifluoromethanesulfonic anhydride dropwise at -40°C under inert gas conditions. Stir at room temperature overnight, dissolve the product with dichloromethane, and then dropwise add n-hexane to precipitate to obtain a polymer (2) with x=0.5 and y=0.5, and then dry in vacuum. 1 H NMR (400MHz, DMSO) δ (ppm) 6.7-7.8 (m, 9.5H), 0.9-1.8 (s, 3H).
[0079] Example 4
[0080] The polymer (1) in Example 2 was dissolved in acetonitrile to obtain a 30 mg / ml solution, which was filtered through a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution, which was spin coated on a silicon substrate to form a film. The uniformity of the film was analyzed by scanning electron microscopy (SEM) and atomic force microscope (AFM), respectively. See attached Figure 1 ,It can be seen from the figure that the obtained film is very uniform and has no crystallization phenomenon.
[0081] Example 5
[0082] The thermal stability of the polymer (1) prepared in Example 2 was measured. The results showed that its decomposition temperature reached above 200°C, and it had good thermal stability. Figure 2 .
[0083] Example 6
[0084] A photoresist formulation and negative development and ultraviolet lithography thereof: The polymer (1) of Example 2 is dissolved in acetonitrile to obtain a solution with a mass concentration of 5%, filtered with a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution, spin-coated on a silicon substrate, baked at 100° C. for 3 minutes, and the prepared film is subjected to an exposure experiment (254 nm) with an exposure time of 1 min. Deionized water is used for development to obtain very clear stripes. Figure 3 The width of the photolithographic stripes is 2 microns.
[0085] Example 7
[0086] A photoresist formulation and negative development and electron beam lithography thereof: The polymer (1) of Example 2 is dissolved in acetonitrile to obtain a solution with a mass concentration of 5%, filtered with a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution, spin-coated on a silicon substrate, baked at 100° C. for 3 minutes, and the prepared film is exposed to electron beams and developed with a developer with a high polarity to obtain very clear stripes (200 nm). Figure 4 .
[0087] Example 8
[0088] A photoresist formulation and its positive development and ultraviolet lithography: The polymer (1) of Example 2 is dissolved in acetonitrile to obtain a solution with a mass concentration of 5%, filtered with a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution, spin-coated on a silicon substrate, baked at 100° C. for 3 minutes, and the prepared film is subjected to an exposure experiment (254 nm) with an exposure time of 1 min. It is developed using isopropanol to obtain very clear stripes. Figure 5 , the width of the lithography stripes is 2 microns.
[0089] Example 9
[0090] A photoresist formulation and its positive development and electron beam lithography: The polymer (1) of Example 2 is dissolved in acetonitrile to obtain a solution with a mass concentration of 5%, filtered with a microporous filter with a pore size of 0.22 μm to obtain a spin coating solution, spin-coated on a silicon substrate, baked at 100° C. for 3 minutes, and the prepared film is exposed to electron beams and developed with a developer with a small polarity to obtain very clear 60 nm stripes. Figure 6 .
[0091] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A styrene sulfonium salt polymer, wherein the repeating unit of the polymer has a structure represented by the following formula (I); Where: x and y represent the percentage of the two monomers in the polymer, x+y=1, 0.3<x≤1; R1 is -S + R3R4, wherein R3 and R4 are the same or different and are independently selected from C 1-15 Alkyl, deuterated C 1-15 Alkyl, aryl; the alkyl, aryl is optionally substituted by one, two or more R1'; each R1' is the same or different and is independently selected from H, C 1-15 Alkyl, C 1-15 Alkoxy; the position of R1 is para, meta or ortho; R2 is selected from H, C 1-15 Alkyl, C 1-15 Alkoxy; q is an integer selected from 1 to 5; X – Selected from halide ion, alkyl sulfonate, haloalkyl sulfonate, p-toluene sulfonate, tetrafluoroborate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide ion.
2. The polymer according to claim 1, characterized in that q is an integer selected from 1-3.
3. The polymer according to claim 1, characterized in that The halogenated alkyl sulfonate is selected from trifluoromethanesulfonate, perfluoropropylsulfonate and perfluorobutylsulfonate.
4. The polymer according to claim 1, characterized in that R1 is selected from the following groups which are unsubstituted or optionally substituted by one, two or more R1': in, Represents the bond between the substituent and the benzene ring in the main structure; R 1a and R 1b The same or different, each independently selected from C 1-15 Alkyl, deuterated C 1-15 Alkyl; R1' has the definition as defined in claim 1.
5. The polymer according to claim 1, characterized in that The repeating unit shown in formula (I) is selected from the following structures: wherein x and y have the definitions as described in claim 1.
6. The method for preparing a polymer according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: The repeating unit is a polymer represented by formula (II): x, y, q, R2 are as defined in any one of claims 1 to 5, reacting with a sulfoxide compound to obtain a polymer having a repeating unit represented by formula (I); The sulfoxide compound is R3-S(=O)-R4; Wherein, R3 and R4 have the definitions as described in any one of claims 1 to 5; The reaction is carried out under the action of a catalyst, and the catalyst is trifluoromethanesulfonic anhydride or trifluoromethanesulfonic acid; In the reaction, the molar ratio of polystyrene or its copolymer to the sulfoxide compound is 1:(0.5-2).
7. The preparation method according to claim 6, characterized in that: The sulfoxide compound is selected from: Among them, R 1a , R 1b The same or different, each independently selected from C 1-15 Alkyl, deuterated C 1-15 alkyl.
8. Use of the polymer according to any one of claims 1 to 5 as a photoresist acid generator or a host material.
9. A photoresist composition comprising the polymer according to any one of claims 1 to 5.
10. The photoresist composition according to claim 9, characterized in that The photoresist composition further comprises a polymer having an acid-sensitive functional group and a photoresist solvent.
11. The photoresist composition according to claim 9, characterized in that The photoresist composition is a single-component photoresist, and the single-component photoresist consists of the polymer according to any one of claims 1 to 5 and a photoresist solvent.
12. The photoresist composition according to claim 11, characterized in that In the single-component photoresist, the x value of the repeating unit represented by formula (I) in the polymer is greater than 0.
5.
13. The photoresist composition according to claim 11, characterized in that The content of the polymer in the single-component photoresist is 1%-50% of the total mass of the photoresist, and the rest is photoresist solvent.
14. The photoresist composition according to claim 10 or 11, characterized in that: The photoresist solvent is selected from one or more of the following substances: cyclohexanone, ethyl n-amyl ketone, ethyl isoamyl ketone, ethanol, acetonitrile, isopropanol, and acetone.
15. A photoresist coating comprising the polymer according to any one of claims 1 to 5.
16. Use of the polymer according to any one of claims 1 to 5, the photoresist composition according to any one of claims 9 to 14 and / or the photoresist coating according to claim 15 in photolithography.
17. The use according to claim 16, characterized in that The application is application in 365nm lithography, 248nm lithography, 193nm lithography, extreme ultraviolet lithography, nanoimprint lithography or electron beam lithography.